La Sistematización De Experiencias Educativas. Una Experiencia Con Docentes Universitarios - Ávila-Meléndez, Lilia Rosa; Cortés-Montalvo, Jorge Abelardo (European Scientific Journal, ESJ, 2017)
In the daily and hectic development of our activities we rarely reserve time to think, rethink, and reflect on the results obtained from our actions, and make crucial decisions about how we can modify the way to change our own actions and with that, transform the context where our professional activity is exercised. A methodological model called the systematization of educational experiences is precisely what gives us this space for collaborative dialogue, and self-reflection and with others. The systematization of experiences is described as a research process where the experiences of the actors are recovered through reflection, dialogue and the reconstruction of events with the purpose of collecting awareness and improving their practices. Present work shows an experience with university professors in a strengths-based training course of critical use of the media. Some of the elements that were used for the construction of the learning and recovery experience were: the logbook, the story, the elaboration of didactic materials, videos and photographs. Collaborative work in triad groups and focus group sessions were some of the techniques used for obtaining and documenting relevant data and information. Following an axis of the systematization of the experience, some of the findings were that the professors recognized the need to be open to change, empathy and collaborative work, to promote the development of critical thinking and the application of knowledge. Participating professors also distinguished innovation and strategy design, such as the development of didactic sequences according to the Model for the Development of Academic Competences (M-DECA), for use in planning of their subjects according to the competence approach and the application of the dimensions of media competition.